IMPLEMENTASI JOYFULL LEARNING DENGAN METODE MIND MAPPING DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI DI SEKOLAH MENENGAH KEJURUAN NEGERI 5 KOTA MALANG - M Saiful Aqil; Azhar Haq; Indhra Musthofa (VICRATINA, 2020)
Islamic and moral Education in every school often considered become boring lesson and full of religious lectures from teachers, as well as in Vocational High Schools 5 Malang. The subjects of Islamic and moral education must be well presented and enjoyable to be practiced wich is it can be well understood by students. The learning process can be run effectively if the learning activities implemented by teachers are able to take student’s passion for learning. With the implementation of Joyfull Learning with Mind Mapping Method in learning Islamic and moral Education as an effort made by the teacher previously designed in the Learning Implementation Plan based on the appeal of vice principal of curriculum to make classroom learning not much different with practicum activities in the workshop or laboratory. To make optimal learning and learning’s objectives can be achieved effectively and efficiently. This research use descriptive qualitative approach with descriptive methode research. The purpose of this study is to describe the implementation, steps, and supporting factors and inhibitors of Joyfull Learning with Mind Mapping Method in the Islamic and moral Education at Vocational High Schools 5 Malang.